If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(a + -1) = 2a + 4(a + -1) Reorder the terms: 5(-1 + a) = 2a + 4(a + -1) (-1 * 5 + a * 5) = 2a + 4(a + -1) (-5 + 5a) = 2a + 4(a + -1) Reorder the terms: -5 + 5a = 2a + 4(-1 + a) -5 + 5a = 2a + (-1 * 4 + a * 4) -5 + 5a = 2a + (-4 + 4a) Reorder the terms: -5 + 5a = -4 + 2a + 4a Combine like terms: 2a + 4a = 6a -5 + 5a = -4 + 6a Solving -5 + 5a = -4 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -5 + 5a + -6a = -4 + 6a + -6a Combine like terms: 5a + -6a = -1a -5 + -1a = -4 + 6a + -6a Combine like terms: 6a + -6a = 0 -5 + -1a = -4 + 0 -5 + -1a = -4 Add '5' to each side of the equation. -5 + 5 + -1a = -4 + 5 Combine like terms: -5 + 5 = 0 0 + -1a = -4 + 5 -1a = -4 + 5 Combine like terms: -4 + 5 = 1 -1a = 1 Divide each side by '-1'. a = -1 Simplifying a = -1
| 5x+8(x+1)+3=11-3x | | 2(7h-3)=120 | | 4-4(x-3)=20 | | 8-5=11 | | -(1-x)=2(3x-1) | | 9y-6+y=-(y+5y) | | 7r+11r=725-7r | | 5(b+1)=5b+1 | | -25=7+4x | | 5(2x-31)+3=10x-155 | | 6(x-8)-3x=5(x-1)-1 | | 3+5-6+2x=-4(x-3)+7 | | -9(4x-2)=108-6x | | 4(2x+2)=7x+1 | | 6x+3x-x=96 | | 2c-11c+5=0 | | 2(m-3)=2(m-6) | | 5x^2-30x+100=0 | | 4(-5-x)=10-2x | | -.25x-9=.90 | | 8-h=-4 | | .28=.04(w-1.0) | | -4-6x=20 | | .28=.04(w-10) | | (3x^3)-(2x^2)= | | 0.4x-3.4=46 | | -.25-9=.90 | | 2x+11=3x+4 | | 3x^3-2x^2= | | -6m+69-9(m+1)=4m-(2m-2)-7m+6 | | 1170=68 | | (X^2+x-6)(x^2+x-2)+3= |